Effective viscoelastic behaviour of rock mass with double-scale discontinuities - Fan, Lifeng (2013)
Effective viscoelastic behaviour of a rock mass with double-scale discontinuities is investigated. The rock mass is modelled as a system of microdefected rock traversed by macrojoints. The effect of microdefects on the dynamic behaviour is evaluated by a viscoelastic equivalent medium model implicitly, whereas the macrojoints in the rock mass are modelled explicitly as physical discontinuities. Therefore, a homogenization–discontinuity combination approach is proposed to investigate the effective viscoelastic behaviour of rock mass under dynamic loading. The effective wave propagation coefficients and the effective viscoelastic complex moduli (storage modulus and loss modulus) are analytically derived. The effects of the double-scale discontinuities on the energy dissipation and the phase velocity are also discussed. It is shown that the effective behaviour of the rock mass with double-scale discontinuities is two-phase viscoelastic. Microdefect and macrojoint have different frequency-sensitive ranges and the effective viscoelastic behaviour is highly related to the stiffness of the discontinuities.